Legitimacy and protest under authoritarianism: explaining student mobilization in Egypt and Morocco during the Arab uprisings. Issue 1 (2nd January 2018) - Thyen, Kressen; Gerschewski, Johannes
ABSTRACT: Political protests constitute a major concern to authoritarian regimes. Existing research has argued that they indicate a lack of regime legitimacy. However, empirical evidence on the relationship between legitimacy and protest participation remains rare. Based on new survey data from Morocco and Egypt, this study investigates whether legitimacy played a significant role in student mobilization during the 2011 uprisings. In doing so, we first develop a context-sensitive concept of legitimacy. This allows us to differentiate the ruler's legitimacy claims and the citizens' legitimacy beliefs. Furthermore, we distinguish between two different objects of legitimacy: the broader political community and specific regime institutions. Our empirical analysis suggests that legitimacy had an independent and significant impact on students' protest participation, yet in more nuanced ways than generally assumed. While protest participation was driven by nationalist sentiments in Egypt, it was motivated by dissatisfaction with the political performance of specific regime institutions in Morocco.